Contempt of Court in Judicial Practice - Muhammad Iqbal Zul Abdi; Andi Istiqlal Assaad; Andi Cakra Cindrapole (COMPENDIUM OF JUDGE MADE LAW, 2025)
This study aims to determine and analyze the forms of contempt that can be categorized as contempt of court in the legal perspective in Indonesia. To determine and analyze the legal basis that regulates contempt of court in the legal system in Indonesia. This study uses the research method used is the Normative research method, namely a legal research method that is sourced from regulatory and secondary document data in the form of collection from library and tertiary materials which are documents containing concepts and information such as dictionaries. The results of this study indicate that 1) Contempt of court is a form of violation of the honor, dignity, and authority of the court, whether carried out inside or outside the courtroom, which can hinder the judicial process and damage public confidence in the judicial system. Enforcement of contempt of court is important to protect the authority and dignity of the judicial institution, so that the court can carry out its judicial functions fairly, without pressure or interference from any party. This act can be a real action or a statement delivered inside or outside the court that can affect the course of the trial or legal process. The act of contempt of court is regulated in statutory regulations, 2) although there are no rules that specifically regulate it, several articles in the Criminal Code regulate the issue of contempt of court such as articles 207, 217, 224 and so on. This research recommendation states that there is a need for more stringent and detailed regulations in the law regarding contempt of court, so that there is legal certainty in taking action against violations of the dignity and authority of the court.